2023
DOI: 10.15252/embr.202256282
|View full text |Cite
|
Sign up to set email alerts
|

LINC00493‐encoded microprotein SMIM26 exerts anti‐metastatic activity in renal cell carcinoma

Abstract: Human microproteins encoded by long non‐coding RNAs (lncRNA) have been increasingly discovered, however, complete functional characterization of these emerging proteins is scattered. Here, we show that LINC00493‐encoded SMIM26, an understudied microprotein localized in mitochondria, is tendentiously downregulated in clear cell renal cell carcinoma (ccRCC) and correlated with poor overall survival. LINC00493 is recognized by RNA‐binding protein PABPC4 and transferred to ribosomes for translation of a 95‐amino‐a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 55 publications
0
2
0
1
Order By: Relevance
“…We hypothesized that some of these lncRNA-derived proteins may be crucial regulatory factors in cancer metastasis and initiated a systematic functional characterization. We previously reported that SMIM26, encoded by LINC00493, exerts anti-metastatic activity by inhibiting AGK-mediated AKT phosphorylation in renal cell carcinoma 26 .…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that some of these lncRNA-derived proteins may be crucial regulatory factors in cancer metastasis and initiated a systematic functional characterization. We previously reported that SMIM26, encoded by LINC00493, exerts anti-metastatic activity by inhibiting AGK-mediated AKT phosphorylation in renal cell carcinoma 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In another study, a micropeptide encoded by ZFAS1 lncRNA was reported to promote the migration of SK-Hep1 hepatocellular carcinoma cells by elevating the levels of intracellular reactive oxygen species [78]. Alongside, overexpression of SMIM26, a microprotein localized in the mitochondria, encoded by LINC00493 lncRNA had exhibited significant anti-metastatic role in clear cell renal cell carcinoma [79]. Parallelly, a 163 amino acid microprotein, pep-AKR1C2, encoded by exo-lncAKR1C2 was reported to drive lymph node metastasis in gastric cancer by regulating fatty acid metabolism [80].…”
Section: Metastasis and Invasionmentioning
confidence: 96%
“…鉴于癌症的高度异质性、高复发率和转移率,针对不同肿瘤亚型的生物特异性标志物亟待开发 [ 38 ] 。与邻近正常组织比较,肿瘤组织中MIAC [ 21 - 22 ] 、SP0495 [ 23 ] 、pTINCR [ 24 ] 、SMIM26 [ 39 ] 等小肽表达下调,而SMIM30 [ 16 - 17 ] 、ATMLP [ 34 ] 、RBRP [ 40 ] 、NoBody [ 41 ] 等表达上调。这些差异表达的lncRNA编码小肽在调节肿瘤能量代谢、血管生成、增殖和转移等方面发挥重要作用,且与癌症预后高度相关,因此可作为癌症生物标志物应用于癌症早期诊断和预后评估。Cai等 [ 42 ] 鉴定出36种在胶质瘤患者和健康人外泌体中差异表达的lncRNA编码小肽,其中患者外泌体中17种小肽缺失、19种小肽过表达。该研究证明循环系统中的lncRNA编码小肽具有作为体液检测新型标志物的巨大潜力。…”
Section: 长链非编码Rna编码小肽的生物医学意义unclassified